Bimetallic NiCo2S4 Nanoneedles Anchored on Mesocarbon Microbeads as Advanced Electrodes for Asymmetric Supercapacitors - Zhang, Yu; Zhang, Yihe; Zhang, Yuanxing; Si, Haochen; Sun, Li (Nano-Micro Letters, 2019)
Bimetallic Ni–Co sulfides are outstanding pseudocapacitive materials with high electrochemical activity and excellent energy storage performance as electrodes for high-performance supercapacitors. In this study, a novel urchin-like NiCo2S4@mesocarbon microbead (NCS@MCMB) composite with a core–shell structure was prepared by a facile two-step hydrothermal method. The highly conductive MCMBs offered abundant adsorption sites for the growth of NCS nanoneedles, which allowed each nanoneedle to fully unfold without aggregation, resulting in improved NCS utilization and efficient electron/ion transfer in the electrolyte. When applied as an electrode material for supercapacitors, the composite exhibited a maximum specific capacitance of 936 F g−1 at 1 A g−1 and a capacitance retention of 94% after 3000 cycles at 5 A g−1, because of the synergistic effect of MCMB and NCS. Moreover, we fabricated an asymmetric supercapacitor based on the NCS@MCMB composite, which exhibited enlarged voltage windows and could power a light-emitting diode device for several minutes, further demonstrating the exceptional electrochemical performance of the NCS@MCMB composite. Highlights: 1 A facile method was used to anchor pseudocapacitive bimetallic NiCo2S4 (NCS) nanoneedles on mesocarbon microbeads (MCMBs), forming a novel urchin-like structure. 2 The NCS@MCMB electrode and an assembled asymmetric supercapacitor displayed good electrochemical performance.